Effect of powder manufacturing process on characteristics of nanostructured MCrAlY coatings: dry vs. wet ball milling - Zakeri, Ali; Tahvili, Pouya; Bahmani, Elnaz; Sabour Rouh Aghdam, Alireza (Journal of Composites and Compounds, 2021)
Metallic MCrAlY coatings have been widely utilized to protect the high-temperature materials operating in aggressive conditions of gas turbines. However, with more demands on the turbine inlet temperature rise for efficiency gains, there is a need to further improve the high-temperature performance of the MCrAlY coatings. A possible way to meet this challenge is by microstructure modification. The aim of this study is to produce nanocrystalline MCrAlY powders via wet and dry mechanical milling techniques and deposit the obtained feedstock powders by the high-velocity oxygen fuel (HVOF) spraying method. Comprehensive characterization and comparison of the different powder processing techniques and the corresponding coatings were studied. It was established that the nano-scaled MCrAlY feedstock powder with low contamination levels could be achieved by mechanical milling. Moreover, the powder samples were well-deposited by the HVOF process and the correlation between powder properties and coating characteristics was investigated.